Deep engineering rock mass grouting simulation similar material based on solid waste and preparation method thereof
By using early-strength grouting simulation similar materials prepared by using solid waste-based slag and desulfurized semi-water gypsum in geotechnical engineering, the problem of flow-solid coupling behavior simulation and cementitious renewability in deep engineering is solved, and high efficiency is achieved. Accurate rock mass simulation test, with green and environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411339790.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing geotechnical engineering grouting simulation similar materials cannot effectively simulate the interaction between the fluid field and the stress field of the rock mass under deep engineering conditions, resulting in distortion of the test results. Common cementitious agents such as cement and gypsum are not renewable and consume huge amounts. Moreover, when the material plasticity is prepared in large-size models, the test is uneven.
Use solid waste-based deep engineering rock mass grouting simulation to simulate similar materials, use slag and desulfurized semi-water gypsum as cementitious agents, combined with silicone oil and other regulators to form early-strength characteristic materials, with mechanical and hydrologic characteristics, suitable for fluid-solid coupling Simulate and flexibly adjust material characteristics through single-component or two-component preparation methods to solve the problems of plasticity and sample homogeneity.
It realizes the flow-solid coupling behavior of the rock mass under deep engineering conditions, reduces gel material consumption, shortens the curing time of the sample, improves the accuracy and reliability of the test results, and has green and environmentally friendly characteristics.
Smart Images

Figure HDA0005059364280000011 
Figure HDA0005059364280000012 
Figure HDA0005059364280000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of geotechnical engineering, and in particular to a similar material for grouting simulation of deep engineering rock mass based on solid waste and a preparation method thereof. Background Art
[0002] Geotechnical engineering has gradually moved to deep areas. Under the influence of high ground stress, high stress difference and engineering excavation disturbance, rock mass is very prone to instability and damage. In severe cases, rock bursts, large deformations and other engineering geological disasters may even occur. Grouting reinforcement technology is an effective means to control deep engineering disasters. By injecting cement slurry into the cracks of the rock mass, the solidified slurry effectively bonds and fills the cracks of the rock mass, which can inhibit the cracks of the surrounding rock from continuing to break and develop deeper, thereby improving the stability and bearing capacity of the surrounding rock as a whole. However, as geotechnical engineering gradually moves to deep areas, its fracture and deformation characteristics are very different from those of shallow areas. Continuing to use the grouting design method of shallow areas is likely to lead to the failure of deep grouting reinforcement projects. Therefore, research on the diffusion and reinforcement mechanism of deep engineering grouting should be carried out according to the grouting conditions of deep engineering.
[0003] However, due to the complex on-site grouting conditions and the fact that the grouting object is actually a large concealed body with complex geological conditions, it is impossible to conduct research on the grouting diffusion mechanism and reinforcement mechanism inside the huge rock mass. Physical model testing is an effective means to study the grouting diffusion and reinforcement mechanism. That is, by combining similarity theory, a material model with properties similar to the on-site original rock mechanics is prepared to simulate the on-site engineering rock mass, simulate the geological elements inside the rock mass inside the model, and bury various required sensors. During the test, the actual on-site working conditions can be reproduced, thereby achieving the purpose of scientific research. For physical model testing, the most important part is actually the research and development of similar simulation materials. Whether similar materials can truly simulate the on-site rock mass is the key factor in determining whether the physical simulation test is successful. To this end, before conducting a grouting simulation test, it is necessary to develop corresponding physical model similar materials.
[0004] At present, physical simulation similar materials with high similarity to rock mass have been developed. These materials are mainly developed for rock mechanical properties, and only consider the mechanical properties of materials such as rock compressive strength, tensile strength, elastic modulus, etc., which are suitable for general physical simulation tests. However, for grouting simulation tests, compared with conventional physical simulation tests, the grouting fluid field is added. Especially under deep engineering conditions, it is actually a fluid-solid coupling test in which the fluid field and the stress field interact with each other. For this reason, similar materials should not only consider the similarity of mechanical properties, but also consider the influence of the fluid field on the material properties. For rocks, the interior is generally denser, and they do not react with the slurry during the grouting process. They will not soften or disintegrate when exposed to water, and their strength properties will not change. However, the conventional similar materials mentioned above cannot meet these requirements at the same time. Solid conventional similar materials may absorb water and weaken their strength. After the liquid slurry loses water, its rheological properties will also cause mutations, which will lead to distortion of physical simulation tests. The test results cannot reflect the real slurry diffusion mechanism. Therefore, it is necessary to develop similar materials for fluid-solid coupling that take into account the hydraulic properties of the rock mass, and it is required that similar materials for fluid-solid coupling simulation grouting also have the above similar properties.
[0005] Regarding the research and development of fluid-solid coupling materials, for example, patent CN112028555A discloses a fluid-solid coupling similar material and its preparation method, the main feature of which is to adjust the mechanical parameter range of the material, but its hydrophysical properties are not disclosed; patents CN103604673A and CN102557551A disclose a fluid-solid coupling similar material and its preparation method for model testing, which better solves the problem of conventional similar materials disintegrating and softening when exposed to water. However, there are still some problems in the utilization of raw materials and preparation methods of similar materials. For example, most of the existing similar material binders use cement and / or gypsum, etc. These binders are non-renewable resources. When the size of the physical model test reaches the meter level or above, the demand for raw materials for a model test is as high as tens of tons, and the consumption of cementitious materials is undoubtedly huge. It is very necessary to seek low-carbon and environmentally friendly cementitious materials to replace cement and gypsum, which is very consistent with the vision of "low carbon" and "carbon neutrality" in today's world. More importantly, during the casting of large models, some cracks or structural surfaces may need to be prefabricated inside the model, and multiple layers of casting are required, which will result in a very slow overall casting rate. During the casting process, the plasticity of the mixed paste-like material will gradually deteriorate or even solidify, which will cause the test to be unable to proceed normally. If the method of preparing the material once for each layer is cast is adopted, it will need to be prepared dozens of times, which will undoubtedly increase the burden on the staff, and there will be certain deviations in the preparation of similar materials each time, resulting in inhomogeneous cast samples and affecting the test results. Summary of the invention
[0006] The purpose of the present invention is to provide a similar material for deep engineering rock grouting simulation based on solid waste and a preparation method thereof. The mechanical properties and hydraulic properties of the material can meet the needs of physical simulation tests. The similar material introduces solid waste to replace conventional cement, gypsum and other materials as a binder, and is a green and environmentally friendly similar material. At the same time, the material has early strength characteristics and can basically reach the final strength of the material in about 7 days, greatly shortening the curing time of the sample. In addition, it is worth noting that the similar material can flexibly adjust the preparation method of the material according to the needs of preparing the physical model, and can be divided into single-component and two-component use, which solves the problem that conventional similar materials lose plasticity and cannot be cast during the preparation of large-scale refined physical models.
[0007] The present invention adopts the following technical solution:
[0008] A similar material for grouting simulation of deep engineering rock mass based on solid waste, wherein the raw materials of the similar material include aggregate, binder, regulator and water, and the regulator is silicone oil, quicklime, activator, retarder, water reducer and accelerator.
[0009] In terms of mass ratio, the aggregate: binder: quicklime: silicone oil: water: activator: water reducer: retarder: accelerator = 80-87.5: 12.5-20: 0.2-0.8: 5-17: 15-30: 0.3-0.7: 0.01-0.02: 0.025-0.04: 0-1.2.
[0010] Furthermore, the aggregate is divided into coarse aggregate and fine aggregate, the coarse aggregate is quartz sand with a fineness of 30 to 40 meshes; the fine aggregate is barite powder with a fineness of 600 to 1000 meshes; the mass ratio of quartz sand to barite powder is 1:1.
[0011] Furthermore, the binder is slag and desulfurized hemihydrate gypsum, and the mass ratio of the slag to the desulfurized hemihydrate gypsum is 1:1; the slag is derived from S95 grade blast furnace slag discharged from power plants, etc., and has a fineness of 800 mesh and above; the desulfurized hemihydrate gypsum is derived from the reprocessed desulfurized gypsum discharged after flue gas desulfurization in power plants, and has a fineness of 300-400 mesh.
[0012] Furthermore, the calcium oxide content in the quicklime in the regulator is not less than 80%, and the fineness is 200 mesh; the activator is solid sodium silicate with a modulus of 3.4; the retarder is sodium gluconate or a protein retarder; the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer; and the quick-setting agent is sodium aluminate or calcium chloride.
[0013] Furthermore, the uniaxial compressive strength of the simulated similar material is dynamically adjusted between 1.21 and 17 MPa, the strain range is 4.2% to 8.8%, the elastic modulus range is 0.2 to 4.71 GPa, the tensile strength is between 0.19 MPa and 1.64 MPa, the brittleness coefficient is 5.34 to 11.4, the softening coefficient is 0.85 and above, and the water absorption rate is 0.4% to 1.96%.
[0014] A method for preparing similar materials for deep engineering rock grouting simulation based on solid waste, the specific steps are as follows:
[0015] (1) Weigh the raw materials according to the mass ratio;
[0016] (2) Pour the weighed raw materials into a cement mortar mixer and mix them evenly to obtain a mixed paste-like material;
[0017] (3) Pour the mixed paste-like material into the prefabricated mold slowly in 3 to 5 times according to the size of the model, and place it on a vibration table or insert a vibration rod into the mold to vibrate for 30 seconds to 60 seconds to eliminate internal bubbles and compact the material;
[0018] (4) After the specimen has hardened, demould it and wrap it with plastic wrap at room temperature for curing to the designed age (7 days, 14 days, 28 days);
[0019] (5) After the sample curing is completed, a similar material based on the deep engineering rock grouting simulation of solid waste is obtained, and the material is placed on a physical model test device to carry out a physical model test.
[0020] Furthermore, if a single-component preparation method is adopted, the step (1) is: weighing, by mass ratio, quartz sand: barite powder: slag: desulfurized hemihydrate gypsum: quicklime: silicone oil: water: activator: water reducer: retarder = 40-43.75: 40-43.75: 6.25-10: 6.25-10: 0.2-0.8: 5-17: 15-30: 0.3-0.7: 0.01-0.02: 0.025-0.04.
[0021] Furthermore, if a two-component preparation method is adopted, the step (1) is:
[0022] Weigh according to the mass ratio: quartz sand: barite powder: slag: activator: water reducer: accelerator: silicone oil: water = 40-43.75: 40-43.75: 12.5-20: 0.6-1.4: 0.01-0.02: 0-1.2: 5-17: 15-30; wherein quartz sand, barite powder, slag, activator, water reducer and accelerator are component A;
[0023] Then weigh according to the mass ratio, quartz sand: barite powder: desulfurized semi-hydrated gypsum: quicklime: retarder: water reducer: silicone oil: water = 40-43.75: 40-43.75: 12.5-20: 0.2-0.8: 0.05-0.08: 0.01-0.02: 5-17: 15-30; wherein quartz sand, barite powder, desulfurized semi-hydrated gypsum, quicklime, water reducer and retarder are component B; the step (2) is: adding silicone oil and water to the component A and component B respectively according to the mass ratio, mixing and stirring evenly to obtain paste-like similar materials A and paste-like similar materials B, and then mixing and stirring the paste-like similar materials A and paste-like similar materials B evenly to obtain a mixed paste-like similar material.
[0024] Furthermore, the stirring in step (2) is performed by stirring at a low speed for 3 minutes and then stirring at a high speed for 1 minute, wherein the low-speed stirring speed is 60 to 65 rpm and the high-speed stirring speed is 120 to 130 rpm.
[0025] Compared with the prior art, the present invention provides a new type of multifunctional fluid-solid coupling grouting simulation similar material based on solid waste as a binder, which is mainly composed of aggregate, binder, water and regulator. Its basic principle is: the binder of this material innovatively introduces solid wastes such as slag and desulfurized semi-hydrated gypsum as a binder, and the aggregates are selected as quartz sand and barite powder. The aggregate and the binder regulate the mechanical properties of similar materials as a whole; at the same time, the alkali-activated product generated by the reaction of slag and desulfurized gypsum has early strength characteristics, which can greatly shorten the curing time of the sample. At the same time, its brittleness and non-softening characteristics are better than those of the consolidation body of gypsum and cement, and can better simulate the mechanical properties of the original rock. The main function of water is to mix and provide the necessary hydration reaction of the binder, and at the same time, the strength of the similar material is adjusted by adjusting the water-solid ratio. The regulator is mainly silicone oil and various admixtures. The role of silicone oil is to reduce the water absorption rate of similar materials, improve the hydrophobicity of the materials, and enable the materials to achieve the purpose of not disintegrating and softening when encountering water, and at the same time, it can also adjust the brittle characteristics of the materials. Various admixtures are mainly used to adjust the plasticity of materials, and are added in proportion according to material requirements. The new multifunctional fluid-solid coupling grouting simulation material comprehensively utilizes solid waste as a cementing material, which not only increases the similarity between similar materials and original rocks, but also provides a new application path for the disposal of solid waste in my country, achieving the goal of green environmental protection and sustainable development. At the same time, the material can flexibly adjust the preparation method and process according to the preparation requirements of the physical model of similar materials. When the physical model preparation requirements are simple, the similar material can be adjusted to a conventional single component to achieve rapid preparation of model samples. When the model sample design is more complex and requires layered and multi-stage refined pouring, the similar material can be divided into two components, A and B. The two components can maintain plasticity for a long time under single-component conditions, and will not react until the two components are mixed, thereby effectively solving the problem that single-component similar materials lose plasticity after long-term stirring and cannot prepare physical model samples. At the same time, it also avoids the phenomenon of performance differences and inhomogeneity between layers of physical model samples caused by multiple preparations of a single component. In terms of mechanical properties and hydraulic characteristics, the new multifunctional fluid-solid coupling grouting simulation material has a wide range of mechanical parameter adjustment, has excellent hydrophobic properties, does not disintegrate or soften when exposed to water, and can achieve similarity to the original rock. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The typical full stress-strain curve of similar materials in the simulation of deep engineering rock mass grouting based on solid waste in Example 1;
[0027] Figure 2 The typical full stress-strain curve of similar materials in the simulation of deep engineering rock grouting based on solid waste in Example 2;
[0028] Figure 3The typical full stress-strain curve of similar materials in the simulation of deep engineering rock grouting based on solid waste in Example 3;
[0029] Figure 4 This is a typical total stress-strain curve of a similar material in the simulation of deep engineering rock grouting based on solid waste in Example 4. DETAILED DESCRIPTION
[0030] The following will be combined with specific implementation methods and examples to specifically explain the technical solution of the present invention, and more clearly present the advantages and various characteristics of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of them. These specific implementation methods and examples are used to illustrate the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A similar material for deep engineering rock mass grouting simulation based on solid waste and its preparation method are carried out in the following steps:
[0033] (1) Weigh the corresponding mass parts of materials, including 1400 parts of quartz sand, 1400 parts of barite powder, 350 parts of slag, 350 parts of desulfurized hemihydrate gypsum, 7 parts of quicklime, 10.5 parts of activator, 1.05 parts of retarder, 0.7 parts of water reducer, 175 parts of silicone oil and 525 parts of water.
[0034] (2) Pour quartz sand, barite powder, slag, desulfurized hemihydrate gypsum, quicklime, activator, retarder and water reducer into a cement mixer and mix them evenly.
[0035] (3) Add silicone oil and water into the above cement mixer in batches and stir thoroughly. Stir at low speed for 3 minutes and then stir at high speed for 1 minute until the materials are uniform.
[0036] (4) Pour the mixed material slowly into the mold in batches and vibrate it on a vibration table for 30s to 60s to eliminate internal bubbles and compact the material.
[0037] (5) After the sample has hardened, remove it from the mold, cover it with plastic wrap, and cure it at room temperature for 7 days.
[0038] (6) After the specimen is cured, it is placed on the physical model test equipment for physical model testing.
[0039] According to the above method, a new type of deep engineering rock grouting simulation similar material based on solid waste is obtained, with a mortar-sand ratio of 4:1 and a solid-liquid ratio of 100:15. When the material is cured at room temperature for 7 days: the uniaxial compressive strength is 17MPa, the strain is 6.84%, the elastic modulus is 4.71GPa, the tensile strength is 1.27MPa, the brittleness coefficient is 11.37, the softening coefficient is 97.5%, and the water absorption rate is 0.44%.
[0040] The stress-strain curve of the new grouting simulation similar material prepared by the above technical solution under uniaxial compression is shown in the attached figure. Figure 1 .
[0041] Example 2
[0042] A similar material for grouting simulation of deep engineering rock mass based on solid waste and a preparation method thereof are carried out in the following steps:
[0043] (1) Materials for component A were weighed as follows: 700 parts of quartz sand, 700 parts of barite powder, 350 parts of slag, 17.5 parts of activator, 0.35 parts of water reducer, 6 parts of accelerator, 157.5 parts of silicone oil and 350 parts of water.
[0044] (2) Materials for component B were weighed as follows: 700 parts of quartz sand, 700 parts of barite powder, 350 parts of desulfurized hemihydrate gypsum, 12 parts of quicklime, 17.5 parts of activator, 0.35 parts of water reducer, 6 parts of retarder, 157.5 parts of silicone oil and 350 parts of water.
[0045] (3) Pour the quartz sand, barite powder, slag, activator, water reducing agent and accelerating setting agent in component A into a cement mixer 1 and mix them evenly.
[0046] (4) Pour the quartz sand, barite powder, desulfurized hemihydrate gypsum, retarder and water reducing agent in component B into cement mixer 2 and mix them evenly.
[0047] (4) Add corresponding amounts of silicone oil and water into the cement mixer 1 and stir thoroughly. Stir at a low speed for 3 minutes and then stir at a high speed for 1 minute until the mixture is uniform.
[0048] (5) Add corresponding amounts of silicone oil and water into cement mixer 2 and stir thoroughly. Stir at low speed for 3 minutes and then stir at high speed for 1 minute until the mixture is uniform.
[0049] (6) Take the materials mixed in cement mixer 1 and cement mixer 2 of equal mass, pour them into cement mixer 3 and stir them thoroughly. Stir at low speed for 3 minutes, and then stir at high speed for 1 minute until the mixture is uniform.
[0050] (7) Pour the mixed material into a prefabricated mold and vibrate it on a vibration table for 30 to 60 seconds to eliminate internal bubbles and compact the material.
[0051] (8) After the sample has hardened, remove it from the mold and wrap it with plastic wrap at room temperature for curing until it reaches 7 days old.
[0052] According to the above method, a new type of solid waste-based deep engineering rock mass fluid-solid coupling grouting simulation similar material is obtained, with a mortar-sand ratio of 4:1 and a solid-liquid ratio of 5:1. When the material is cured at room temperature for 7 days, the uniaxial compressive strength is 7.14MPa, the strain is 6.43%, the elastic modulus is 1.89GPa, the tensile strength is 0.67MPa, the brittleness coefficient is 10.41, the softening coefficient is 91.6%, and the water absorption rate is 0.89%.
[0053] The stress-strain curve of the new fluid-solid coupling grouting simulation similar material prepared by the above technical solution under uniaxial compression conditions is shown in the attached figure. Figure 2 .
[0054] Example 3
[0055] A similar material for deep engineering rock mass grouting simulation based on solid waste and its preparation method are carried out in the following steps:
[0056] (1) Weigh the corresponding mass parts of materials, including 1400 parts of quartz sand, 1400 parts of barite powder, 350 parts of slag, 350 parts of desulfurized hemihydrate gypsum, 21 parts of quicklime, 24.5 parts of activator, 1.05 parts of retarder, 0.7 parts of water reducer, 455 parts of silicone oil and 875 parts of water.
[0057] (2) Pour quartz sand, barite powder, slag, desulfurized hemihydrate gypsum, quicklime, activator, retarder and water reducer into a cement mixer and mix them evenly.
[0058] (3) Add silicone oil and water into the above cement mixer in batches and stir thoroughly. Stir at low speed for 3 minutes and then stir at high speed for 1 minute until the materials are uniform.
[0059] (4) Pour the mixed material slowly into the mold in batches and vibrate it on a vibration table for 30s to 60s to eliminate internal bubbles and compact the material.
[0060] (5) After the sample has hardened, remove it from the mold, cover it with plastic wrap, and cure it at room temperature for 7 days.
[0061] (6) After the specimen is cured, it is placed on the physical model test equipment for physical model testing.
[0062] According to the above method, a new type of solid waste-based deep engineering rock grouting simulation similar material is obtained, with a mortar-sand ratio of 4:1 and a solid-liquid ratio of 4:1. When the material is cured at room temperature for 7 days: the uniaxial compressive strength is 3.08MPa, the strain is 5.57%, the elastic modulus is 0.85GPa, the tensile strength is 0.4MPa, the brittleness coefficient is 7.52, the softening coefficient is 97.46%, and the water absorption rate is 1.03%.
[0063] The stress-strain curve of the new fluid-solid coupling grouting simulation similar material prepared by the above technical solution under uniaxial compression conditions is shown in the attached figure. Figure 3 .
[0064] Example 4
[0065] A similar material for deep engineering rock mass grouting simulation based on solid waste and its preparation method are carried out in the following steps:
[0066] (1) Weigh the corresponding mass parts of materials, including 1458 parts of quartz sand, 1458 parts of barite powder, 291 parts of slag, 291 parts of desulfurized hemihydrate gypsum, 23 parts of quicklime, 21 parts of activator, 0.87 parts of retarder, 0.58 parts of water reducer, 175 parts of silicone oil and 700 parts of water.
[0067] (2) Pour quartz sand, barite powder, slag, desulfurized hemihydrate gypsum, quicklime, activator, retarder and water reducer into a cement mixer and mix them evenly.
[0068] (3) Add silicone oil and water into the above cement mixer in batches and stir thoroughly. Stir at low speed for 3 minutes and then stir at high speed for 1 minute until the materials are uniform.
[0069] (4) Pour the mixed material slowly into the mold in batches and vibrate it on a vibration table for 30s to 60s to eliminate internal bubbles and compact the material.
[0070] (5) After the sample has hardened, remove it from the mold, cover it with plastic wrap, and cure it at room temperature for 7 days.
[0071] (6) After the specimen is cured, it is placed on the physical model test equipment for physical model testing.
[0072] According to the above method, a new type of deep engineering rock grouting simulation similar material based on solid waste is obtained, with a mortar-sand ratio of 5:1 and a solid-liquid ratio of 5:1. When the material is cured at room temperature for 7 days: the uniaxial compressive strength is 5.02MPa, the strain is 6.65%, the elastic modulus is 1.29GPa, the tensile strength is 0.63MPa, the brittleness coefficient is 7.74, the softening coefficient is 94.68%, and the water absorption rate is 1.02%.
[0073] The stress-strain curve of the similar material prepared by the fluid-solid coupling grouting simulation under uniaxial compression is shown in the attached figure. Figure 4 .
Claims
1. A similar material for grouting simulation of deep engineering rock mass based on solid waste, characterized in that: The raw materials of the similar materials include aggregate, binder, regulator and water, and the regulator is silicone oil, quicklime, activator, retarder, water reducer and quick-setting agent.
2. The similar material for deep engineering rock mass grouting simulation based on solid waste according to claim 1, characterized in that: In terms of mass ratio, the aggregate: binder: quicklime: silicone oil: water: activator: water reducer: retarder: accelerator = 80-87.5: 12.5-20: 0.2-0.8: 5-17: 15-30: 0.3-0.7: 0.01-0.02: 0.025-0.04: 0-1.
2.
3. The similar material for deep engineering rock mass grouting simulation based on solid waste according to claim 1, characterized in that: The aggregate is divided into coarse aggregate and fine aggregate. The coarse aggregate is quartz sand with a fineness of 30 to 40 meshes; the fine aggregate is barite powder with a fineness of 600 to 1000 meshes; the mass ratio of quartz sand to barite powder is 1:
1.
4. The similar material for deep engineering rock mass grouting simulation based on solid waste according to claim 1, characterized in that: The binder is slag and desulfurized hemihydrate gypsum, and the mass ratio of the slag to the desulfurized hemihydrate gypsum is 1:1; the slag comes from S95 grade blast furnace slag discharged from power plants, etc., and has a fineness of 800 mesh and above; the desulfurized hemihydrate gypsum comes from the reprocessed desulfurized gypsum discharged after flue gas desulfurization in power plants, and has a fineness of 300-400 mesh.
5. The similar material for grouting simulation of deep engineering rock mass based on solid waste according to claim 1, characterized in that: The calcium oxide content of quicklime in the regulator is not less than 80%, and the fineness is 200 mesh; the activator is solid sodium silicate with a modulus of 3.4; the retarder is sodium gluconate or a protein retarder; the water reducer is a naphthalene water reducer or a polycarboxylic acid water reducer; and the quick-setting agent is sodium aluminate or calcium chloride.
6. The similar material for grouting simulation of deep engineering rock mass based on solid waste according to claim 1, characterized in that: The uniaxial compressive strength of the simulated similar material is dynamically adjusted between 1.21 and 17 MPa, the strain range is 4.2% to 8.8%, the elastic modulus range is 0.2 to 4.71 GPa, the tensile strength is between 0.19 MPa and 1.64 MPa, the brittleness coefficient is 5.34 to 11.4, the softening coefficient is 0.85 and above, and the water absorption rate is 0.4% to 1.96%.
7. A method for preparing similar materials for deep engineering rock mass grouting simulation based on solid waste according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: (1) Weigh the raw materials according to the mass ratio; (2) Pour the weighed raw materials into a cement mortar mixer and mix them evenly to obtain a mixed paste-like material; (3) Pour the mixed paste-like material into the prefabricated mold slowly in 3 to 5 times according to the size of the model, and place it on a vibration table or insert a vibration rod into the mold to vibrate for 30 seconds to 60 seconds to eliminate internal bubbles and compact the material; (4) After the specimen has hardened, demould it and wrap it with plastic wrap at room temperature for curing to the designed age (7 days, 14 days, 28 days); (5) After the sample curing is completed, a similar material based on the deep engineering rock grouting simulation of solid waste is obtained, and the material is placed on a physical model test device to carry out a physical model test.
8. The method for preparing similar materials for deep engineering rock mass grouting simulation based on solid waste according to claim 7, characterized in that: If a single-component preparation method is adopted, the step (1) is: weighing, according to the mass ratio, quartz sand: barite powder: slag: desulfurized hemihydrate gypsum: quicklime: silicone oil: water: activator: water reducer: retarder = 40-43.75: 40-43.75: 6.25-10: 6.25-10: 0.2-0.8: 5-17: 15-30: 0.3-0.7: 0.01-0.02: 0.025-0.
04.
9. The method for preparing similar materials for deep engineering rock mass grouting simulation based on solid waste according to claim 7, characterized in that: If a two-component preparation method is adopted, the step (1) is: Weigh according to the mass ratio: quartz sand: barite powder: slag: activator: water reducer: accelerator: silicone oil: water = 40-43.75: 40-43.75: 12.5-20: 0.6-1.4: 0.01-0.02: 0-1.2: 5-17: 15-30; wherein quartz sand, barite powder, slag, activator, water reducer and accelerator are component A; Then weigh according to the mass ratio, quartz sand: barite powder: desulfurized semi-hydrated gypsum: quicklime: retarder: water reducer: silicone oil: water = 40-43.75: 40-43.75: 12.5-20: 0.2-0.8: 0.05-0.08: 0.01-0.02: 5-17: 15-30; wherein quartz sand, barite powder, desulfurized semi-hydrated gypsum, quicklime, water reducer and retarder are component B; the step (2) is: adding silicone oil and water to the component A and component B respectively according to the mass ratio, mixing and stirring evenly to obtain paste-like similar materials A and paste-like similar materials B, and then mixing and stirring the paste-like similar materials A and paste-like similar materials B evenly to obtain a mixed paste-like similar material.
10. The method for preparing similar materials for deep engineering rock mass grouting simulation based on solid waste according to claim 7, characterized in that: The stirring in step (2) is performed by stirring at a low speed for 3 minutes and then stirring at a high speed for 1 minute. The low-speed stirring speed is 60 to 65 rpm, and the high-speed stirring speed is 120 to 130 rpm.
Citation Information
Patent Citations
Softrock-like material and preparation method
CN101614629A
Bi-component dry powdery geopolymer grouting material based on all-solid waste and preparation method of bi-component dry powdery geopolymer grouting material
CN115745486A
Preparation method of low-permeability rock stratum similar material large-size model test piece
CN117268870A
Iron spar powder, guartz sand cement rock-soil similar material and preparation process thereof
CN1792990A
Reproducing method of actual base rock stress state
JP1985263832A
